Antibacterial Activity of Curcumin-Loaded Copper Nanoparticles Against Multidrug- Resistant UTI Causing Staphylococcus Aureus: Life Sciences -Microbiology - Ishwarya, Dr. R.; Kamala, N.; Manipriya, K.; K.V. Leela, Dr. (International Journal of Life Science and Pharma Research, 2023)
The production of biofilms by bacteria like S.aureus is frequent, and it leads to various treatment resistance. Plants and vegetables have more benefits in the green synthesis of nanoparticles (CuNPs) since they are safe to handle and easily accessible. The objective of the present study is to analyze the antibacterial activity of Curcumin-loaded Copper Nanoparticles [Cur-Cu-NPs] against S.aureus, which causes multidrug-resistant UTIs. Physical analysis (Scanning Electron Microscope [SEM]) and Chemical analysis (X-Ray Diffraction [XRD] and Fourier Transform Infrared [FTIR]) have all been used to validate the synthesis of Cur-Cu-NPs. The discovery of virulence factors that might be used as targets for vaccine and therapeutic development is a critical stage in this process. Curcumin, a ready-made compound which act as reducing and capping agents in the conversion of silver nitrate to CuNPs. The function of biomolecules in bioreduction and effective stabilization of CuNPs was established by FTIR. The crystalline character of the produced CuNPs with [FCC] Face centered cubic structure may be seen in XRD patterns. CuNPs produced with an average particle size of 140-190 nm had a spherical form, according to SEM examination. The efficacy of green-generated nanoparticles derived from aqueous extract against the UTI-causing Staphylococcus aureus strain was assessed in the clearance of micro titre wells during Minimum Inhibitory concentration analysis in μg/ml. These green synthesized Copper nanoparticles had significant antibacterial activity. The present study is supportive evidence that the synergistic additive medications result in best bactericidal actions with fewer adverse effects.